Indoor radon determination in dwellings located at Dikili geothermal area in western Turkey - Yarar, Y; Günaydi, T; Çelebi, N (LIPPINCOTT WILLIAMS & WILKINS, 2005)
This paper presents the indoor radon concentrations in dwellings located in the Dikili geothermal area in western Turkey. Indoor radon monitoring was performed for 3 mo using 121 detectors installed in the living rooms and bedrooms of 62 houses selected from the region. A passive time-integrating radon measuring technique was applied by using CR-39 solid-state nuclear track detectors. Average indoor radon levels for the houses varied from 31 to 280 Bq m(-3). Corresponding annual effective doses were calculated, and risks for lung cancer due to inhalation of indoor radon were estimated.
Keywords: Rn-222, indoor; effective dose; lungs, human; cancer; Environmental Sciences & Ecology; Public, Environmental & Occupational Health; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging